2010
DOI: 10.1002/stem.319
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β and Notch Signaling Mediate Stem Cell Differentiation into Smooth Muscle Cells

Abstract: The differentiation of stem cells into smooth muscle cells (SMCs) plays an important role in vascular development and remodeling. In addition, stem cells represent a potential source of SMCs for regenerative medicine applications such as constructing vascular grafts. Previous studies have suggested that various biochemical factors, including transforming growth factor-β (TGF-β) and the Notch pathway, may play important roles in vascular differentiation. However, the interactions of these two signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
190
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(199 citation statements)
references
References 40 publications
9
190
0
Order By: Relevance
“…4a, only upregulation of MLCK was observed. SMA and ACTA1, which were smooth/skeletal muscle markers for smooth/skeletal muscle differentiation [38], were not upregulated. It corresponded well with the real-time PCR result in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…4a, only upregulation of MLCK was observed. SMA and ACTA1, which were smooth/skeletal muscle markers for smooth/skeletal muscle differentiation [38], were not upregulated. It corresponded well with the real-time PCR result in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Inducible activation of NICD in mESCs cultured under mesoderm differentiation conditions leads to a reduction of endothelial, haematopoietic and cardiac differentiation and favours the generation of smooth muscle cells (SMC) (Nemir et al, 2006;Schroeder et al, 2003Schroeder et al, , 2006. Activation of the NOTCH pathway in human mesenchymal or ESCs similarly induces SMC differentiation (Kurpinski et al, 2010). In the chick embryo, NOTCH activity in the ventral mesoderm mediates the balance between blood or endothelial and smooth muscle progenitors, and promotes the formation of the latter (Shin et al, 2009).…”
Section: Notch Signalling Regulates the Acquisition Of Distinct Mesodmentioning
confidence: 99%
“…NOTCH activity is notably required to maintain a pool of neural progenitors and to inhibit further neural differentiation, but can also regulate the acquisition of distinct cell fates by promoting gliogenesis or influencing binary fate choices during neurogenesis (reviewed by Pierfelice et al, 2011;Yoon and Gaiano, 2005). A role for the NOTCH pathway during early neural specification has been pinpointed by gain-and loss-of-function in vitro analyses showing that NOTCH activity promotes neural lineage commitment in pluripotent ESCs (Das et al, 2010;Kurpinski et al, 2010;Lowell et al, 2006). In order to investigate whether the NOTCH pathway can also play such an early role during in vivo neural development, we analysed the formation of neurectodermal tissue in N1ICD epi embryos.…”
Section: Notch Activation Induces Neural Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…3h-l), which further confirmed that EGFP − cells in tunica media were MVSCs. To determine whether MVSCs could differentiate into mature SMCs and turn on EGFP expression, we activated Notch signalling by co-culturing EGFP − MVSCs with OP9-Delta1 feeder cells 34 . After 2 weeks of co-culture, majority of the MVSCs showed strong green fluorescence (Fig.…”
Section: Resultsmentioning
confidence: 99%